2017
DOI: 10.5114/aoms.2016.63751
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma concentrations of interleukin 35 in patients with coronary artery disease

Abstract: IntroductionAtherosclerosis leading to coronary artery disease (CAD) is a chronic inflammatory condition. Interleukin 35 (IL-35) released by regulatory T cells (Tregs) has been found to be associated with CAD in the Chinese population. However, nothing is known about the relation between IL-35 concentrations and cholesterol levels. The aim of the study was to assess the levels of IL-35 in CAD patients and healthy subjects from a Caucasian population, and to analyze the relationship between IL-35 and the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…44 autoimmune thrombocytopenia, 45 periodontitis, 46 and coronary artery diseases. 47 The results of the present study also showed that there was significant difference between PU, AS, and NHS groups with respect to the distribution of the genotypes and alleles at rs3761548 in the Several SNPs were placed in the promoter, intron, and exon regions of the FOXP3 gene. 29 When SNPs are situated in the promoter region, they could impair gene expression through affecting the transcription process.…”
Section: Il-35 Is Identified As An Anti-inflammatory and Immunosuppresupporting
confidence: 65%
See 1 more Smart Citation
“…44 autoimmune thrombocytopenia, 45 periodontitis, 46 and coronary artery diseases. 47 The results of the present study also showed that there was significant difference between PU, AS, and NHS groups with respect to the distribution of the genotypes and alleles at rs3761548 in the Several SNPs were placed in the promoter, intron, and exon regions of the FOXP3 gene. 29 When SNPs are situated in the promoter region, they could impair gene expression through affecting the transcription process.…”
Section: Il-35 Is Identified As An Anti-inflammatory and Immunosuppresupporting
confidence: 65%
“…However, elevated levels of IL‐35 were reported in patients with hepatitis B virus infection, especially in those with higher viral load, in patients with active tuberculosis, in patients with leprosy, and in patients with malignant diseases . Furthermore, circulating levels of IL‐35 are aberrant in patients with multiple sclerosis (MS), allergic asthma, inflammatory bowel disease, autoimmune thrombocytopenia, periodontitis, and coronary artery diseases …”
Section: Discussionmentioning
confidence: 99%
“…IL-35 inhibits inflammatory response. Both are associated with the modulating effects of IL-1 ( 14 , 15 ). Studies have shown that overexpression of IL-1 can induce the release of higher levels of IL-23 by hepatocytes and macrophages, and cause disorders of lipid metabolism, triggering formation of an inflammatory microenvironment ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to clinical experiments, as an anti-inflammatory cytokine, IL-35 expression in mouse atherosclerotic plaques was significantly increased . A small number of other studies, however, have reported increased IL-35 expression in atherosclerotic plaques and serum in ApoE mice fed with a high-fat diet, as well as in the plasma of patients with coronary artery disease (Gorzelak-Pabiś et al, 2017;Li et al, 2018). Using a mouse model of atherosclerosis, administration of recombinant mouse IL-35 significantly decreased plaque area in the aortic root, and Treg immune responses were also found to be enhanced (Tao et al, 2016).…”
Section: Animal Studiesmentioning
confidence: 94%
“…81760051 to YL). Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Wang et al, 2014;Subramanian et al, 2015;Tao et al, 2016;Gorzelak-Pabiś et al, 2017;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Li et al, 2018;Ryu et al, 2018;Huang et al, 2019;Wang et al, 2019…”
Section: Fundingmentioning
confidence: 99%